Correlation between Apoptosis and Histological Grade of Transitional Cell Carcinoma of Urinary Bladder - Jalali Nadoushan, Mohammadreza; Peivareh, H; Azizzadeh Delshad, A (Urology Journal, 2009)
Purpose: ToÂ evaluateÂ theÂ relationshipÂ between histologicalÂ gradeÂ andÂ apoptoticÂ index (AI)Â inÂ Â transitionalÂ cellÂ carcinomaÂ (TCC) of urinary bladder. Materials and Methods: Formalin-fixedÂ andÂ paraffin-embeddedÂ tissueÂ blocksÂ from 75Â Â Â Â patientsÂ withÂ TCC, who undergoneÂ transurethralÂ resection (TUR)Â wereÂ studied.Â Â Â Â Â Â One 3-micron section was provided from each TUR samples.Â InÂ oneÂ sectionÂ afterÂ hematoxylinÂ andÂ eosinÂ Â (H&E)Â staining,Â tumor gradeÂ was determinedÂ accordingÂ toÂ World Health Organization/International Society of Urology and Pathology (WHO/ISUP)Â criteria.Â TheÂ apoptoticÂ Â cellsÂ wereÂ determinedÂ usingÂ aÂ terminalÂ deoxynucleotidylÂ transferase (TdT)Â mediatedÂ dUTPÂ biotinÂ nickÂ endÂ labeling (TUNEL)Â technique.Â ApoptoticÂ indexÂ wasÂ thenÂ obtainedÂ Â Â Â asÂ theÂ percentÂ ofÂ TUNELÂ positiveÂ cellsÂ fromÂ observationsÂ ofÂ atÂ leastÂ 1000Â cellsÂ inÂ Â eachÂ section. Results: Forty-nine patients were men and 26 were women.Â Mean age was 56.34?9 years.Â Â Mean AI was 2.30?0.50.Â The relationship between grade and AIÂ Â was significant (p=0.000, r=0.551); a higher grade was associated with a higher AI. Conclusion: Apoptosis index has a positive correlation with bladder TCCâ€™s grade.Â Further studies are needed to better determine the effect of apoptosis index on prognosis.